A Study of Health, Medicines, Hygiene and Etiquette in Ancient India - Singh, Siddhartha (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
Background: This paper explores health, hygiene, medicine, morality and social etiquette of the people in the contemporary societies in ancient India focusing on the accounts of Chinese pilgrims Yuan Chwang (629-645 A.D.) and I-tsing (671-695), the two pilgrims who visited India during 7th Century. Objective: The paper aims to explore the travelogue of the Chinese visitors as the primary source of the article which is abound with the information in regard to health, hygiene and dietary habits including medicinal practices, moral practices and social etiquettes practiced by the monastic and non-monastic people in the contemporary societies in ancient India. Methodology: Library based methodology of historical research, textual analysis, and comparative cultural study have been applied to complete this article. Result: Yuan Chwang gives details of personal cleanliness, dietary rules, and measures for treatment of illness during 7th century India whereas I-tsing gives accounts of health practices - exercises, diet and medicine - in Buddhist monasteries. The paper compares the health practices of ancient India and contemporary China focusing on spiritual and physical discipline and their contribution in maintaining well-being of the people in the society. Conclusion: The paper explores the prevalence of healthy characteristics in the societal people, like cleanliness, cultural values, morality, reverence and self-discipline, in both physical and spiritual world, in the societies of India during that time.